Orderly disorder in magic-angle twisted trilayer graphene - Turkel, Simon; Swann, Joshua; Zhu, Ziyan; Christos, Maine; Watanabe, K.; Taniguchi, T.; Sachdev, Subir; Scheurer, Mathias S.; Kaxiras, Efthimios; Dean, Cory R.; Pasupathy, Abhay N. (Science (American Association for the Advancement of Science), 2022)
Magic-angle twisted trilayer graphene (TTG) has recently emerged as a platform to engineer strongly correlated flat bands. We reveal the normal-state structural and electronic properties of TTG using low-temperature scanning tunneling microscopy at twist angles for which superconductivity has been observed. Real trilayer samples undergo a strong reconstruction of the moiré lattice, which locks layers into near–magic-angle, mirror symmetric domains comparable in size with the superconducting coherence length. This relaxation introduces an array of localized twist-angle faults, termed twistons and moiré solitons, whose electronic structure deviates strongly from the background regions, leading to a doping-dependent, spatially granular electronic landscape. The Fermi-level density of states is maximally uniform at dopings for which superconductivity has been observed in transport measurements. Stacking and twisting graphene layers with respect to each other can lead to exotic transport effects. Recently, superconductivity was observed in graphene trilayers in which the top and bottom layers are twisted with respect to the middle layer by the same, “magic” angle. Turkel et al . used scanning tunneling microscopy to take a closer look into the stacking structure. They found that a small misalignment between the top and bottom layers caused the lattice to rearrange itself into a pattern of triangular domains. The domains had a magic-angle twisted trilayer structure and were separated by a network of line and point defects. —JS Scanning tunneling microscopy reveals lattice reconstruction in a moire material.